Pemanfaatan Media Sosial Instagram Oleh BNBP Dalam Upaya Mitigasi Bencana - Erfan Wahyudi (IPDN Kampus NTB, 2024)
In the era of technological advancement and digitalization, public access to various information has become increasingly facilitated through social media. Social media platforms, such as Instagram, are considered effective tools to meet the trending information needs. The use of Instagram is not confined solely to individuals and businesses; it extends to various institutions, including the National Disaster Management Agency (BNPB). BNPB, as a governmental body, leverages Instagram as a means to disseminate information related to natural disasters and mitigation efforts. This research aims to comprehend the impact of BNPB's utilization of Instagram in the context of disaster mitigation within the community. The research methodology employed is a qualitative descriptive approach, involving the observation of BNPB's Instagram account and interviews with one of its followers, namely bnpb_indonesia. This qualitative study focuses on observing and analyzing the social environment from an individual perspective. The research findings indicate that the Instagram account bnpb_indonesia serves as an effective platform for disseminating information regarding natural disasters. Through this account, the public can stay updated on the latest news concerning natural disasters and receive education on disaster mitigation methods. BNPB actively employs Instagram as a means of socialization to educate the public about the importance of awareness regarding regions prone to disasters.